A new freshwater chrysophyte, Chrysomorula cohaerens gen. et sp. nov. (Chrysophyceae, Chrysocapsaceae) from North America - Wujek, Daniel E. (Phytotaxa, 2013)
A new freshwater chrysophyte genus and species, Chrysomorula cohaerens, is described from the United States. Chrysomorula cohaerens is a distinct taxon of non-motile heterokont chrysophyte. It forms macroscopic mucilaginous colonies attached to aquatic macrophytes, filamentous algae, and other substrata. Each colony is initially held together forming a hollow sphere by the confluence of its cell walls. The colony is at first a sphere, becoming ovoid to irregular with growth in size. Thus, it differs from other similar chrysophyte genera such as Heimiochrysis and Chalkopyxis. Cells bear pseudocilia.